Postemergent Herbicides for Use in Ornamentals - Jeffrey G. Norcini; Chris Marble (EDIS)
Postemergent herbicides are applied directly to weeds. This revised 4-page fact sheet is largely comprised of two tables: Table one lists postemergent herbicides that can be safely used over the top of some ornamentals when used according to label directions; table 2 lists postemergent herbicides that are registered for use around ornamental plants when applied as a directed spray. Written by Jeffrey G. Norcini and Chris Marble, and published by the UF Department of Environmental Horticulture, November 2014. (UF/IFAS photo: Thomas Wright)